2018
DOI: 10.32382/mf.v14i1.144
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Metode Konsumsi Dengan Peramalan, Eoq, MMSL Dan Analisis Abc-Ven Dalam Manajemen Perbekalan Farmasi Di Rumah Sakit Pelamonia Makassar

Abstract: Kepmenkes RI No. 1197/Menkes /SK/ 2004 tentang Standar Pelayanan Farmasi di Rumah Sakit. Penelitian ini bertujuan untuk menentukan nilai EOQ, Safety Stock dan ROP untuk mencegah stagnasi dan stockout. Kemudian membandingkan nilai stok sebelum dan sesudah dilakukan simulasi perencanaan dan pengendalian perbekalan farmasi pada RS Pelamonia Makassar. Penelitian ini merupakan penelitian kualitatif dengan menggunakan teknik nonprobability sampling, yaitu snowball sampling dan purposive sampling.Sedangkan teknik ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Hasilnya diketahui terdapat selisih antara kondisi saat ini dengan hasil EOQ yang lebih kecil dibandingkan perhitungan perusahaan. Penelitian yang dilakukan [11], EOQ digunakan dengan Safety Stock dan ROP agar tidak terjadi stockout atau stagnasi. Hasilnya diketahui bahwa melalui perhitungan yang dilakukan terjadi peningkatan efisiensi dibandingkan kondisi saat ini.…”
Section: Pendahuluanunclassified
“…Hasilnya diketahui terdapat selisih antara kondisi saat ini dengan hasil EOQ yang lebih kecil dibandingkan perhitungan perusahaan. Penelitian yang dilakukan [11], EOQ digunakan dengan Safety Stock dan ROP agar tidak terjadi stockout atau stagnasi. Hasilnya diketahui bahwa melalui perhitungan yang dilakukan terjadi peningkatan efisiensi dibandingkan kondisi saat ini.…”
Section: Pendahuluanunclassified
“…The EOQ method is used to determine the quantity of inventory orders minimizing order costs and storage costs. 8 This research was previously conducted by Veronica M. Dampung (2018) and the results found that there is a plan system that has been calculated with previous calculations and inventory control has been carried out more efficiently in managing pharmaceutical supplies in public pharmacies Pelamonia Hospital Pharmacy Installation Menu shows a decrease in stock value, the TOR figure is getting higher and the ratio of inventory stock to used inventory is getting smaller. 9 Another study has also been conducted at the XXX Hospital Pharmacy Installation in Mojokerto City obtained the average results of inventory value in 2016-2018 with the most efficient inventory value with the largest difference when compared to real inventory value.…”
Section: Introductionmentioning
confidence: 97%
“…Data on planning, procurement and use of BPJS Kesehatan patient drugs in 2018 were analyzed using the EOQ method then compared with the value of the ineachuse parameter can reduce the Stock Out value, but the effectiveness and efficiency of drug control were not achieved. 8 Based on the initial survey that had previously been conducted at Royal Prima Marelan General Hospital, no calculations had been made using the application of consumption methods with EOQ, MMSL and ABC-VEN forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…Excess inventory value (overstock) causes waste in inventory. Based on research conducted by Dampung et al [6], the application of the method can increase the efficiency of drug supplies as indicated by the inventory value that shows a significant difference in the group before the application of the method, as much as 4,835,087,839; thus, there is a decrease in the inventory value of 2,540,410,122. The value of drug supplies in 2019 and 2020 at the pharmaceutical installation of X Private Hospital in Waru, Sidoarjo Regency, was quite high due to the increasing number of patients visiting the hospital.…”
Section: Introductionmentioning
confidence: 99%